Return on Sales for Companies in Eastern Poland - Wierzbicka, Wioletta (Olsztyn Economic Journal, 2015)
This study has been performed in order to assess the return on sales for business enterprises in Eastern Poland, compared to companies in other Polish regions, and to explore how values of this metric have changed between 2007 and 2013. The findings can be summarized as follows: in 2007-2013, the gross return on sales generated by companies in the provinces of Eastern Poland, as well as elsewhere in the country, decreased. However, the dynamics of these changes varied greatly between individual provinces. Within the whole conglomeration of the Polish provinces, certain processes of internal convergence and divergence could be distinguished. Divergent processes were identified in two provinces located in Eastern Poland, namely the Lubelskie region and the Podlaskie region, while the other three provinces in the same part of Poland (Podkarpackie, Świętokrzyskie and Warmińsko-Mazurskie) were observed to undergo convergent processes.